Seismological Observations on Amplitude‐Dependent Energy Dissipation in the Crust and Uppermost Mantle - Hayato Tero; Junichi Nakajima (Geophysical Research Letters)
Abstract The amplitude‐dependent seismic attenuation in the crust and uppermost mantle was investigated using spectral analysis of crustal and intraslab earthquakes that occurred in two areas in northeastern Japan. P‐wave attenuation (Q−1) was found to be weakly proportional to amplitude (A) in both areas, following the relationship, Q−1∝An. Quantitative analysis reveals that amplitude‐dependent attenuation is more pronounced in the uppermost mantle (n ∼ 0.16) than in the crust (n ∼ 0.05). This depth‐dependent behavior of attenuation may be attributed to increasing temperature and pressure, which enhance dislocation density and mobility. Our findings challenge the common assumption of amplitude‐independent attenuation. Although we infer dislocation mechanisms as the primary cause of the amplitude‐dependent energy dissipation, further experimental studies under high temperature and pressure conditions are necessary for better understanding of the complex nature of seismic attenuation and the underlying processes.